Case studies on longitudinal mercury content in humpback whale (Megaptera novaeangliae) baleen. Issue 1 (January 2022) - Lowe, Carley L.; Jordan-Ward, Renee; Hunt, Kathleen E.; Rogers, Matthew C.; Werth, Alexander J.; Gabriele, Chris; Neilson, Janet; von Hippel, Frank A.; Buck, C. Loren
Abstract: Quantification of contaminant concentrations in baleen whales is important for individual and population level health assessments but is difficult due to large migrations and infrequent resighings. The use of baleen allows for a multiyear retrospective analysis of contaminant concentrations without having to collect repeated samples from the same individual. Here we provide case studies of mercury analysis using cold vapor atomic absorption spectroscopy in three individual humpback whales ( Megaptera novaeangliae ), a 44.5-year-old female and two males aged ≥35 and 66 years, over approximately three years of baleen growth. Mercury concentrations in the female's baleen were consistently 2–3 times higher than in either male. Age did not affect mercury concentrations in baleen; the younger male had comparable levels to the older male. In the female, mercury concentrations in the baleen did not change markedly during pregnancy but mercury did spike during the first half of lactation. Stable isotope profiles suggest that diet likely drove the female's high mercury concentrations. In conclusion, variations in baleen mercury content can be highly individualistic. Future studies should compare sexes as well as different populations and species to determine how the concentrations of mercury and other contaminants vary by life history parameters and geography. Abstract : Marine; Mammal; Mercury; Toxicology; Whale; Physiology; Baleen.